Quantitative interactome analysis with chemical cross-linking and mass spectrometry. (February 2022) - Wippel, Helisa H.; Chavez, Juan D.; Tang, Xiaoting; Bruce, James E.
Abstract: Structural plasticity and dynamic protein–protein interactions are critical determinants of protein function within living systems. Quantitative chemical cross-linking with mass spectrometry (qXL-MS) is an emerging technology able to provide information on changes in protein conformations and interactions. Importantly, qXL-MS is applicable to complex biological systems, including living cells and tissues, thereby providing insights into proteins within their native environments. Here, we present an overview of recent technological developments and applications involving qXL-MS, including design and synthesis of isotope-labeled cross-linkers, development of new liquid chromatography–MS methodologies, and computational developments enabling interpretation of the data. Graphical abstract: Image 1 Highlights: Quantitative chemical cross-linking provides information on changes in protein interactomics. Overview of recent technological developments involving qXL-MS. Applications of qXL-MS in biological systems with varying conditions.